Cognitive Outcomes for Congenital Hypothyroid and Healthy Children: A Comparative Study - ORDOOEI, Mahtab; MOTTAGHIPISHEH, Hadi; FALLAH*, Razieh; RABIEE, Azar (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Ordooei M, MottaghiPisheh H, Fallah R, Rabiee A. Cognitive Outcomes for Congenital Hypothyroid and Healthy Children: A Comparative Study. Iran J Child Neurol. 2014 Autumn;8(4): 28-32. Abstract Objective Early diagnosis and treatment of congenital hypothyroidism (CH) and the prevention of developmental retardation is the main goal of public health national screening programs. This study compares the cognitive ability of children with CH diagnosed by neonatal screening with a healthy control group (2007) in Yazd, Iran. Materials & Methods In a case-controlled study, the intelligent quotient (IQ) of 40 five-year-old children with early treated CH and good compliance were evaluated by the Wechsler preschool and primary scale of intelligent test and compared to 40 healthy age and gender matched children as controls. Results 22 boys (55%) and 18 girls (45%) in both groups were evaluated. In children with CH, 19 (47.5%) and 21 (52.5%) persons had transient and permanent hypothyroidism, respectively. Range of TSH and T4 level at the onset of diagnosis were 11.41–81 mu/l and 1.50–14.20 μg/dl, respectively.The intelligence levels of all children with CH were within the average or normal range and IQs ranged from 91–108. Children with CH had lower full-scale IQs (107.25 ± 2. 9 versus 110.50 ± 2.66, p=0.001), verbal IQ (106.95 ± 3.5 versus 109.90 ± 3.44, P-value=0.001) and performance IQ (106.3 ± 3.68 versus 108.87 ± 3.70) than the control group.However, no statistically significant differences were observed for mean IQ scores in permanent and transient CH. Conclusion Children with CH who had early treatment and good compliance had normal cognitive abilities, but may have a decreased IQ relative to the healthy control group. References LeFranchi S. Hypothyroidism. Kliegman RM, Stanton BF, Schor NF, St. Geme JW, Behrman RE. Nelson Textbook of Pediatrics. Philadelphia, Saunders 2011; 19th edition, Pp: 1895-1900. Nouri-Shadkam M, Jafarizadeh M, Mirzaei M, Motlagh M.E, Eslami Z, Afkhami-Ardekani M, et al. Prevalence of congenital hypothyroidism and transient increased levels of TSH in Yazd province. J Shahid Sadoughi Univ Med Sci 2008; 16:15-20. [Article in Persian] Hashemipour M, Hovsepian S, Kelishadi R, Iranpour R, Hadian R, Haghighi S, et al. Permanent and transient congenital hypothyroidism in Isfahan-Iran. J Med Screen 2009; 16:11-6. Dalili S, Rezvany SM, Dadashi A, Medghalchi A, Mohammadi H, Dalili H, et al. Congenital hypothyroidism: a review of the risk factors. Acta Med Iran 2012; 50:735-9. Zeinalzadeh AH, Talebi M. Neonatal screening for congenital hypothyroidism in East Azerbaijan, Iran: the first report. J Med Screen 2012; 19:123-6. Karamizadeh Z, Saneifard H, Amirhakimi G, Karamifar H, Alavi M. Evaluation of congenital hypothyroidism in Fars province, Iran. Iran J Pediatr 2012; 22:107-12. Bargagna S, Canepa G, Costagli C, Dinetti D, Marcheschi M, Millepiedi S, et al. Neuropsychological follow-up in early-treated congenital hypothyroidism: a problemoriented approach. Thyroid 2000; 10:243-9. van der Sluijs Veer L, Kempers MJ, Maurice-Stam H, Last BF, Vulsma T, Grootenhuis MA. Health- related quality of life and self-worth in 10-year old children with congenital hypothyroidism diagnosed by neonatal screening. Child Adolesc Psychiatry Ment Health 2012; 6:32. Soliman AT, Azzam S, Elawwa A, Saleem W. Linear growth and neurodevelopmental outcome of children with congenital hypothyroidism detected by neonatal screening: A controlled study. Indian J Endocrinol Metab 2012; 16:565-8. Bongers-Schokking JJ. Influence of timing and dose of thyroid hormone replacement on mental, psychomotor, and behavioral development in children with congenital hypothyroidism. J Pediatr 2005; 147:768-74. Wechsler, D. The Wechsler Preschool and Primary Scale of Intelligence - Manual. New York: psychological Corporation, 1967. Romero JB, Palacios GC, Gómez N, Silva A, Fabela JH. Intelligence quotient related with congenital hypothyroidism etiology. Rev Med Inst Mex Seguro Soc 2011; 49:179-83. [Article in Spanish] Kik E, Noczyńska A. Evaluation of mental development of children with congenital hypothyroidism detected in screening test--personal observations. Pediatr Endocrinol Diabetes Metab 2010; 16:100-8. [Article in Polish] Arenz S, Nennstiel-Ratzel U, Wildner M, Dörr HG, Intellectual outcome, motor skills and BMI of children with congenital hypothyroidism: a population-based study. Acta Paediatr 2008; 97:447-50. Alvarez González MA, Carvajal Martínez F, Pérez Gesén C, Olivares Torres A, Fernández Yero JL, Robaina Alvarez R, et al. Prognosis of cognition in congenital hypothyroidism following early treatment. Double effect hypothesis. Rev Neurol 2004, 16-31; 38:513-7. [Article in Spanish] Boileau P, Bain P, Rives S, Toublanc JE. Earlier onset of treatment or increment in LT4 dose in screened congenital hypothyroidism: which as the more important factor for IQ at 7 years? Horm Res 2004; 61:228-33. Salerno M, Militerni R, Bravaccio C, Micillo M, Capalbo D, Di MS, Tenore A. Effect of different starting doses of levothyroxine on growth and intellectual outcome at four years of age in congenital hypothyroidism. Thyroid 2002; 12:45-52. Dimitropoulos A, Molinari L, Etter K, Torresani T, Lang- Muritano M, Jenni OG, Largo RH, Latal B. Children with congenital hypothyroidism: long-term intellectual outcome after early high-dose treatment. Pediatr Res 2009; 65:242-8. Joseph R. Neuro-developmental deficits in early-treated congenital hypothyroidism. Ann Acad Med Singapore 2008; 37(12 Suppl):42-3. Kempers MJ, van der Sluijs Veer L, Nijhuis-van der Sanden MW, Kooistra L, Wiedijk BM, Faber I, et al.Intellectual and motor development of young adults with congenital hypothyroidism diagnosed by neonatal screening. J Clin Endocrinol Metab2006; 91:418-24. Rovet JF. Children with congenital hypothyroidism and their siblings: do they really differ? Pediatrics 2005;115:e52-7. Kempers MJ, van der Sluijs Veer L, Nijhuis-van der Sanden RW, Lanting CI, Kooistra L, Wiedijk BM, et al. Neonatal screening for congenital hypothyroidism in the Netherlands: cognitive and motor outcome at 10 years of age. J Clin Endocrinol Metab2007; 92:919-24. Azizi F, Afkhami M, Sarshar A, Nafarabadi M. Effects of transient neonatal hyperthyrotropinemia on intellectual quotient and psychomotor performance. Int J Vitam Nutr Res 2001; 71:70-3. Salerno M, Militerni R, Di Maio S, Bravaccio C, Gasparini N, Tenore A. Intellectual outcome at 12 years of age in congenital hypothyroidism. Eur J Endocrinol 1999; 141:105-10. Hsiao PH, Chiu YN, Tsai WY, Su SC, Lee JS, Soong WT. Intellectual outcome of patients with congenital hypothyroidism detected by neonatal screening. J Formos Med Assoc 2001; 100: 40-4.